Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 2. Beitrag. Bibliographie zur entomologischen Erforschung Albaniens. - Königsmann, Eberhard (Contributions to Entomology = Beiträge zur Entomologie, 1962)
The bibliography contains 524 titles of entomological literature on Albania, arranged in alphabetical order after the authors' names. The citation (author, title, periodical) is followed by a reference to the respective insect order dealt with. Publications from the title of which it is not quite obvious, how far they touch the insect fauna of Albania, are briefly explained.